Po liteness across cultures and languages — a contrastive study of Norwegian and English - Awedyk, Witosław (Folia Scandinavica Posnaniensia, 2007)
This paper discusses verbal realization of one request situation which has been used in the empirical part of my doctoral dissertation (Awedyk 2001) which sets out to compare and contrast request strategies in the realization of the speech act of request in Norwegian and English. The present article is a continuation of the discussion on request strategies I touched upon in my previous article (Awedyk 2003).